A SELECTIVE AND SENSITIVE LC-MS/MS METHOD FOR QUANTIFICATION OF FOUR POTENTIAL GENOTOXIC IMPURITIES IN ATAZANAVIR SULFATE DRUG SUBSTANCE IN TRACE LEVEL - N., SIVA JYOTHI; MUVVALA, VENKATNARAYANA (International Journal of Applied Pharmaceutics, 2021)
Objective: The main objective of current research work is to develop and validate a rapid, sensitive and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the trace analysis of four potential genotoxic impurities in Atazanavir Sulfate drug substance. Methods: LC-MS/MS analysis of four potential genotoxic impurities was done on Acquity UPLC CSH C18 (100 mm × 2.1 mm, 1.7 μm) column. In this method, mobile phase A (10 mM ammonium acetate) mobile phase B (methanol: acetonitrile (90:10, v/v) with gradient run with the flow rate of 0.2 ml/min. The method was developed with the short run time of 13 min. Triple quadrupole mass detector coupled with positive electrospray ionization was used for the quantification of genotoxic impurities in multiple reaction monitoring (MRM) mode. Results: The method was linear in the range of 0.3 ppm to 4.5 ppm for BOC Hydrazine Acid impurity, BOC Epoxide and Keto impurity with a correlation coefficient not less than 0.9994. The accuracy of the method was in the range of 99.26% to 105.71% for all four potential genotoxic impurities (PGIs). No impurities were identified in the Atazanavir Sulfate active pharmaceutical ingredient sample. Conclusion: The proposed method is specific, linear, precise, accurate, robust and stable for the quantification of the four genotoxic impurities at very low levels.